Sistem Pendukung Keputusan Pemilihan Calon Penerima Program Indonesia Pintar Dengan Metode Fuzzy TOPSIS - Ainaya, Regina; Gustian, Dudih (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Smart Indonesia Program Assistance is educational assistance provided by the government to elementary, middle and high school students aged 6-12 years. The Smart Indonesia Program is an improvement from the previous government program, namely Assistance for Poor Students. This assistance is one of the existing aids at the MI Salakopi school, but the school is still having difficulties in determining the students who are entitled to the Smart Indonesia Program (PIP). This problem is due to the same criteria and the selection is still manually by the school operator. In addition, in previous studies, there were several similar rankings, of course reducing the level of objectivity and accuracy of research based on the results of direct observations of prospective beneficiaries. The combination of the Fuzzy Topsis method is expected to provide a solution, especially in reducing the same ranking data so that the accuracy of objectivity is better. The Fuzzy Topsis method can reduce the results of the same ranking to 46%. The final result of the calculation using Fuzzy TOPSIS which was tested on 15 alternatives with the highest value of A12 of 0.658